2016
DOI: 10.1080/01658107.2016.1203340
|View full text |Cite
|
Sign up to set email alerts
|

Non-arteritic Anterior Ischaemic Optic Neuropathy after Uneventful Cataract Extraction

Abstract: We present the case of a 74-year-old Caucasian female who suffered sudden visual loss after routine phacoemulsification cataract surgery. The patient was subsequently diagnosed with nonarteritic anterior ischaemic optic neuropathy. The case is described in detail, and a concise review of the literature is presented together with the authors' view on the subject outlined. This is a very rare complication after cataract surgery even in high-risk patients with associated systemic comorbidities. We suspect that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Clinically, there have been certain reports of ischemic optic neuropathy occurring after cataract surgery and leading to a sudden decline in VA (3,4). Another study suggested that the macular vascular system was essential to visual function (5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinically, there have been certain reports of ischemic optic neuropathy occurring after cataract surgery and leading to a sudden decline in VA (3,4). Another study suggested that the macular vascular system was essential to visual function (5).…”
Section: Discussionmentioning
confidence: 99%
“…Phacoemulsification combined with intraocular lens implantation is an effective treatment method to improve VA (2). However, certain patients with cataracts experience a decrease in VA at different time-points after surgery (3,4). For instance, Emeriewen et al (3) studied the decreased VA after cataract surgery caused by ischemic optic neuropathy and reported that hypertension, diabetes, cerebrovascular disease and high levels of lipids were systemic risk factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in macular vascular density (VD) and blood flow areas after gravity-based phacoemulsification may affect the recovery of visualacuity [5] . Emeriewen et al [6] reported that patients experienced a decrease in visual acuity at different timepoints caused by ischemic optic neuropathy, using a gravitybased phacoemulsification system. Li et al [7] also indicated that there was a significant reduction in the superficial retinal VD in patients with myopia after cataract surgery.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have reported that the cystoid macular edema was found after FLACS [ 2 , 3 ]. Moreover, Emeriewen et al [ 4 ] studied that patients experienced a decrease in visual acuity at different time-points caused by ischemic optic neuropathy after conventional cataract surgery. Li et al [ 5 ] indicated that there was a signi cantly reduction in super cial retinal vessel density in patients with myopia after conventional cataract surgery.…”
Section: Introductionmentioning
confidence: 99%